Microstructure and mechanical properties of micro-resistance spot welding between stainless steel 316L and Ti-6Al-4V - Mansor, Muhammad Safwan Mohd; Yusof, Farazila; Ariga, Tadashi; Miyashita, Yukio (Springer Verlag, 2018)
In this study, austenitic stainless steel 316L and titanium alloy (ASTM grade 5) were welded together by micro-resistance spot welding at different combinations of welding parameters and by using specifically designed electrode geometry. The welded joints were subjected to tensile shear strength test in order to determine the strength of the welded zones. In addition, micro-hardness and microstructural examinations of the fracture mode (failure analysis) were carried out in order to examine the influence of welding parameters on the welded joints. The results showed that using a combination of 2.0 kN welding current, 100 ms welding time, and 241 N welding force yield the highest load value, 378.25 N by using full factorial design of experiment (DOE). Welding current is the most significant parameter which is obtained through analysis of variance (ANOVA). However, the increase in welding current should be controlled to avoid weld metal expulsion. The microstructure of these resistance-welded metals are detailed and investigated by using SEM and EDS mapping analysis. Based on the SEM observations, columnar dendritic structures can be seen at the fusion zone (FZ) of the welded nugget.